Hubungan Antara Self Control Dan Konformitas Teman Sebaya Terhadap Perilaku Delinkuen Status - J.W, M.Vicryrahman; Ariffudin, Imam; Nur Rahmawati, Ajeng Intan (Syifaul Qulub: Jurnal Bimbingan dan Konseling Islam, 2025)
This study aims to determine the relationship between self-control and peer conformity to delinquent status behavior in grade VII students at SMPN 2 Probolinggo Regency. This study uses a quantitative approach with an explanatory research type. The population in this study were all grade VII students of SMPN 2 Probolinggo Regency totaling 128 students. A sample of 56 students was taken using random sampling technique. Data analysis was carried out using Pearson correlation test and multiple linear regression with the help of SPSS software version 25. The results showed that there was a negative and significant relationship between self-control and delinquent status behavior with a correlation coefficient value of -0.702 (p <0.05). This means that the higher the level of student self-control, the lower their tendency to truant. Likewise, peer conformity also has a negative and significant relationship to delinquent status behavior with a correlation coefficient value of -0.625 (p <0.05). The results of multiple linear regression analysis show that self-control and peer conformity together contribute 77% to status delinquent behavior (R² = 0.770), while the remaining 23% is influenced by other factors outside this study. This finding confirms the importance of strengthening self-control and developing a positive friendship environment in efforts to prevent status delinquent behavior in students at SMPN 2 Dringu, Probolinggo Regency.